Analysis of the effect of human development index components on economic growth - Pawer Darasa Panjaitan; Darwin Damanik (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study aims to determine the effect of the components of the human development index on the economic growth of Pematangsiantar City. The method used in this study is a quantitative method and uses an ordinary least square multiple regression model. The data used is secondary data obtained from the Central Statistics Agency (BPS). In this study, the analysis used was a multiple regression analysis model. The results showed that the health index had a positive and significant effect on economic growth in Pematangsiantar City, the education index had a positive and insignificant effect on economic growth in Pematangsiantar City, the purchasing power index had a positive and significant impact on economic growth in Pematangsiantar City, and the Human Development Index ( health index, education index, and purchasing power index) have a positive and significant effect on economic growth in Pematangsiantar City. The coefficient of determination obtained by the Adjusted R20.9909 indicates that the value of the health variable, education variable, and purchasing power variable can explain the variation of the economic growth variable in Pematangsiantar City by 99.09%, while the remaining 0.91% is explained by other variables outside research model.